Indonesian government policies in digital entrepreneurship transformation - Ida Zubaedah; Eka Wahyu Hidayat (The International Journal of Politics and Sociology Research, 2022)
Covid-19 has resulted in the paralysis of various sectors of the community's economy. The Indonesian government immediately made efforts to restore the community's economy through the development of digital entrepreneurship. The method used in this study is a library research. The data used in this study are secondary data in the form of books, scientific journals and various relevant references. The study results show that entrepreneurship has a very important role for a country, the transformation of digital entrepreneurship in Indonesia is supported by government policies that are able to encourage economic growth. In Indonesia there are several successful entrepreneurs in the digital era, namely Nadiem Makarim (Go-Jek), Ahmad Zaky (Bukalapak), Andrew Darwis (Kaskus), William Tanuwijaya (Tokopedia), and Ferry Unardi (Traveloka).